Pengaruh Kemampuan Manajemen dan Karakteristik Usaha terhadap Kinerja Usaha UKM Olahan Produk Salak di Kabupaten Banjarnegara - astuti, windi -; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2016)
The purpose of this study was to determine whether there was an effect simultaneously or partial management capabilities and characteristics of the business to business performance SMEs processed thorny palm products in Banjarnegara. The sample used was the whole subject that is as much as 32 SMEs. The dependent variable in this research is the business performance (Y) while the independent variable includes management capabilities (X1) and business characteristics (X2). Methods of data collection is using the questionnaire. Data were analyzed using descriptive statistical analysis and regression analysis. The results showed that management capabilities and business characteristics influence simultaneously on the business performance significantly value of 0.000 < 0,05. Partial effect was also found in the independent variable on the dependent variable. Management capabilities affect the business performance significantly value of 0,017 < 0,05. Business characteristics affect the business performance significantly value.